Pedal peptide/orcokinin‐type neuropeptide signaling in a deuterostome: The anatomy and pharmacology of starfish myorelaxant peptide in Asterias rubens. Issue 18 (6th September 2017) - Lin, Ming; Egertová, Michaela; Zampronio, Cleidiane G.; Jones, Alexandra M.; Elphick, Maurice R.
Abstract: Pedal peptide (PP) and orcokinin (OK) are related neuropeptides that were discovered in protostomian invertebrates (mollusks, arthropods). However, analysis of genome/transcriptome sequence data has revealed that PP/OK‐type neuropeptides also occur in a deuterostomian phylum—the echinoderms. Furthermore, a PP/OK‐type neuropeptide (starfish myorelaxant peptide, SMP) was recently identified as a muscle relaxant in the starfish Patiria pectinifera . Here mass spectrometry was used to identify five neuropeptides (ArPPLN1a‐e) derived from the SMP precursor (PP‐like neuropeptide precursor 1; ArPPLNP1) in the starfish Asterias rubens . Analysis of the expression of ArPPLNP1 and neuropeptides derived from this precursor in A. rubens using mRNA in situ hybridization and immunohistochemistry revealed a widespread pattern of expression, with labeled cells and/or processes present in the radial nerve cords, circumoral nerve ring, digestive system (e.g., cardiac stomach) and body wall‐associated muscles (e.g., apical muscle) and appendages (e.g., tube feet and papulae). Furthermore, our data provide the first evidence that neuropeptides are present in the lateral motor nerves and in nerve processes innervating interossicular muscles. In vitro pharmacological tests with SMP (ArPPLN1b) revealed that it causes dose‐dependent relaxation of apical muscle, tube foot and cardiac stomach preparations from A. rubens . Collectively, these anatomical and pharmacological data indicate that neuropeptides derived from ArPPLNP1 act as inhibitory neuromuscular transmitters in starfish, which contrasts with the myoexcitatory actions of PP/OK‐type neuropeptides in protostomian invertebrates. Thus, the divergence of deuterostomes and protostomes may have been accompanied by an inhibitory–excitatory transition in the roles of PP/OK‐type neuropeptides as regulators of muscle activity. Abstract : Localization and pharmacological characterization of neuropeptides derived from a pedal peptide/orcokinin (PP/OK)‐type precursor protein in the starfish Asterias rubens (phylum Echinodermata) indicates that they act as inhibitory neuromuscular transmitters (e.g., in tube feet, as illustrated here). This contrasts with excitatory effects of PP/OK‐type neuropeptides in protostomian invertebrates (e.g., mollusks, arthropods).